Endobronchial Ultrasoud Guided Transbronchial Needle Aspiration - Dhungana, Ashesh; Shrestha, Prajowl; Shrestha, Kiran; Shah, Shristi; Karki, Pratikchya; Upreti, Harish Chandra (Journal of Nepal Health Research Council, 2018)
Evaluation of mediastinal lymphadenopathy is often challenging. Endobronchial Ultrasound (EBUS) is a novel technique which provides real time sonographic guidance during Transbronchial Needle Aspiration (TBNA) from mediastinal and hilar lesions. A 60-year-old smoker presented with two months history of cough and chest pain on the right side. CT thorax revealed a right upper lobe spiculated mass with paratracheal (Station 4R) and subcarinal (Station 7) lymph nodes. Bronchoscopy did not reveal any endobronchial mass. Since EBUS-TBNA is superior to conventional TBNA for malignant mediastinal node, an EBUS- TBNA was performed from both lymph node stations. . Cytopathology and histopathology revealed non-small cell lung cancer. We hereby report the first use of EBUS-TBNA in Nepal, in a patient with lung cancer and mediastinallymphadenopathy.